Vibration Analysis on the Bridge Structures Caused by Train Load - Marpaung, Bangun; Kusumawardani, Rini (Semarang State University, 2020)
Abstract: The Muktiharjo Kaligawe railway bridge or BH 9 which located in KM 3+450 is truss bridge that has a special function,that is as a railway network where the BH 9 is a bridge with the steel frame type. Tests and analysis are done on two points of the bridge structures, those are in one third span of the bridge’s structure and another in the middle span of the bridge’s structure. The acceleration of vibration when the sensor accelerometer placed in one third part of the bridge’s structure influenced Y the most. While the acceleration of vibration when the sensor accelerometer placed in the middle part of the bridge’s structure influenced Z the most. The maximum acceleration in the one third part of the bridge structure where the Argo Anggrek train with the speed of 47 mph has the maximum acceleration towards X of 1.346270 m/s2, the maximum acceleration towards Y is 1.639314 m/s2, and the maximum acceleration towards Z is 1.315038 m/s2. Meanwhile the maximum acceleration where the accelerometer placed in the middle part of the bridge, Argo Anggrek train with the speed of 49 mph has the maximum acceleration toward X of 1.053043 m/s2, the maximum acceleration towards Y is 0.631594 m/s2, and the maximum acceleration towards Z is 1.191879 m/s2. The maximum acceleration when the accelerometer placed in the middle part of the bridge, Maharani train with the speed of 45 mph has the maximum acceleration towards X of 1.231041 m/s2, the maximum acceleration towards Y is 1.425204 m/s2, and the maximum acceleration towards Z is 1.319857 m/s2. Meanwhile the maximum acceleration when the accelerometer placed in the middle part of the bridge where Maharani train pass with the speed of 46 mph has the maximum acceleration towards X of 0.509838 m/s2, the maximum acceleration towards Y is 0.639036 m/s2, and the maximum acceleration towards Z is 1.073661 m/s2.